2019
DOI: 10.3389/fimmu.2019.02317
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Function and Composition Changes of Immune Cells During Normal and Pathological Pregnancy at the Maternal-Fetal Interface

Abstract: A successful pregnancy requires a fine-tuned and highly regulated balance between immune activation and embryonic antigen tolerance. Since the fetus is semi-allogeneic, the maternal immune system should exert tolerant to the fetus while maintaining the defense against infection. The maternal-fetal interface consists of different immune cells, such as decidual natural killer (dNK) cells, macrophages, T cells, dendritic cells, B cells, and NKT cells. The interaction between immune cells, decidual stromal cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
254
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(270 citation statements)
references
References 148 publications
1
254
0
2
Order By: Relevance
“…Teng et al [3] hypothesized that the pathogenesis of pregnancy-induced HLH was similar to preeclampsia, where the immature placenta releases genetically foreign material into the maternal circulation. Additionally, these functional alterations can affect placental apoptosis and syncytial integrity, as well as induce preeclampsia, intrauterine growth retardation, or fetal death [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Teng et al [3] hypothesized that the pathogenesis of pregnancy-induced HLH was similar to preeclampsia, where the immature placenta releases genetically foreign material into the maternal circulation. Additionally, these functional alterations can affect placental apoptosis and syncytial integrity, as well as induce preeclampsia, intrauterine growth retardation, or fetal death [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have shown that changes in the DICs are partly due to the resident population of endometrium, and partly due to the recruitment of peripheral immune cells. 27,60,61 The mechanism of recruitment of these DICs has yet to be fully elucidated, although a series of research articles have reported that chemokines are critical in the trafficking and maintenance of DICs. 27,62,63 During pregnancy, an increase in the number of NK cells in the decidua recruited from the periphery occurs, and it is generally recognized that NK cells that express CXCR4 may be recruited from the periphery to the uterus by trophoblast-derived CXCL12.…”
Section: Effect Of Cxcl16 On Immune Cell Recruitmentmentioning
confidence: 99%
“…However, in RSA decidua their portion raises to more than one fold of the normal counterpart. Besides, they exert enhanced production of pro-inflammatory cytokines, which is likely causing the decidual environment harmful to the fetal cells and other maternal immune cells such as T cells and macrophages (Fridman et al, 2012;Fu et al, 2013;Ma et al, 2017;Sotnikova et al, 2014;Yang et al, 2019).…”
Section: Comparison Of the Differential Gene Expression In Dnk Subsetmentioning
confidence: 99%